Effects of seed dressing and fertilizer on the common bean yields, Bean stem maggot and Root rot diseases in Southern highlands of Tanzania - Kato, Fred; Lwehabura, Jovin; Seenga, Rehema.O; Kabungo, David; Kilango, Michael; Mukankusi, Clare; Rubyogo, Jean-Claude (2021)
Common bean (Phaseolus vulgaris.L) is an important legume crop mainly for smallholder farmers in Tanzania, for home consumption and cash income. Nevertheless, the bean production in the Southern Highlands of Tanzania which contributes approximately 24.3% of the total bean country production is constrained by both abiotic and biotic factors. Among the most devastating biotic constraints includes the insect pests such as bean fly (Ophiomyia phaseoli), bean foliage beetle (Ootheca bennigseni) and aphids (Aphis fabae) and diseases such as bean root rots (BRR), while among the abiotic factors, the soil fertility was most prevalent. Two hundred- thirty (230) on-farm trials were established in seven bean growing districts to test the effects of seed dressing using an insecticide/fungicide Apron Star and an inorganic fertilizer-Yara Mila on crop performance (diseases, BSM incidence and grain yield) of five popular improved bean varieties and one farmer’s preferred variety as a check. BSM and BRR incidences and severities were evaluated at the flowering stage while the yield was done at harvest stage. It was also observed that the incidences of both BRR and BSM in the non-treated plots were significantly (P < 0.05) higher than the fertilizer applied alone, seed dressed alone, seed dressed and fertilizer applied plots. Similarly, plots treated with Apron Star and fertilizer combination exhibited the highest total yield of dry weight than the fertilizer alone, seed dresser alone and non-treated plot. All the improved bean varieties performed significantly (P < 0.05) higher than the farmers’ varieties. Njano Uyole showed better performance in diseases, pest incidence and yield among the improved varieties with or without dressing and fertilizers.